Disturbance of intracardiac hemodynamics in children with chronic rheumatic cardiac disease - Kondratiev V.A.; Porokhnya N.H.; Kunak Ye.V. (Medičnì Perspektivi)
By means of Doppler echocardiography there have been studied disturbances of intracardiac hemodynamics in 44 children aged 8-17 years with chronic rheumatic cardiac disease and developed mitral aortal and combined heart defects, as well as in chronic rheumatic cardiac disease without developed valvar defect. Differential approach has been defined to administration of inhibitors of angiotensin-converting factor in rheumatic heart defects: developed insufficiency of mitral and/or aortal valves II-III stage leads to remodeling of the left heart portions with developing chronic insufficiency of blood circulation, being an index for prolonged, not less than a year usage of the angiotensin-converting factor. In the presence of isolated mitral regurgitation, I stage in children with chronic rheumatic cardiac disease usage of the angiotensin-converting factor may be cancelled due to insignificant disturbances of valvar hemodynamics and a small risk of developing blood circulation insufficiency. Timely sanation of chronic infection foci in nasopharynx (conservative and surgical treatment of chronic tonsillitis, adenoid vegetations, therapy of hemolytic streptococcus presence) decreases risk of developing rheumatic heart defect in children suffered acute rheumatic fever.